An awareness study of HIV/AIDS among adolescent students of Chitwan district, Nepal - Singh, S.K.; Manandhar, N.; Prasai, M.; Patowary, S.; Krishna, G. (Journal of Institute of Medicine Nepal, 2007)
A cross sectional study was conducted among the adolescent students of 12 randomly selected higher secondary school of Chitwan district, Nepal with an objective to assess the awareness by studying their knowledge and attitude towards the disease. It is really very gratifying to note that 100.0% of the respondents had heard about the disease and majority of them (95.0% ) had correct knowledge about the causative agents. Among the respondents quite large number of students (79.0%) knew about high risk age group and 81.0% were aware about safe sex as one of the major preventive measure. The attitude of respondents towards the AIDS patients was firmly positive. Among them 84.5% had no objection in treating AIDS patients in the general hospital with extra precaution. The main source of their information, education and communication were from electronic media. These observations were indicative of good awareness about the disease which will definitely help in bringing about behavioral change at the individual level and will go in a long way for prevention of transmission amongst the high risk groups and to contain its spread. Journal of Institute of Medicine Vol.27(3) 2005